Bionomics and control of sorghum shoot fly ,Atherigona varia socatta rond - KARAMJIT Singh (Ludhiana P.A.U, 1970)
The eggs were laid on the underside of the leaves Incubation period varied from 20-48 hrs The newly hatched larvae bored into the plant tissue The larva passed through 3 instars Pupation took place in the shoot near the base of the plant and rarely in the
Keywords: ENTOMOLOGY; ATHERIGONA VARIA; BIONOMICS; ENTOMOLOGY; ENTOMOLOGY; SORGHUM; SORGHUM - DISEASES AND PESTS